The parameters of Fibonacci and Lucas cubes - Ilić, Aleksandar (Ars mathematica contemporanea, 2017)
Motivated by the conjectures from Castro, et al. in 2011, in this paper we use integer programming formulations for computing the domination number, the 2-packing number and the independent domination number of Fibonacci cubes and Lucas cubes for ?$n \le 13$?.
Keywords: dominacijsko število; Fibonaccijevi kubi; Lucasovi kubi; število 2-pakiranj